2007
DOI: 10.1016/j.cellbi.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of carnitine in breast cancer via decreasing arginase activity and increasing nitric oxide

Abstract: Breast cancer remains one of the most common types of cancer. High levels of arginase and ornithine in different carcinomas may indicate their relation to cancer. Carnitine is a cofactor required for the transformation of free long-chain fatty acids into acetyl-carnitines. We have examined the protective effect of carnitine and the possibility that it disturbs arginase-nitric oxide (NO) interaction. Histopathological examination, arginase activity, ornithine and NO levels were determined in tumour tissues. Mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…In line with this finding, Erbas et al (2007) reported that L-carnitine increased NO through reducing the activity of arginase and elevating that of NO synthase. Another study reported by Sharifi et al (2009) indicated that L-carnitine reduced the activity of angiotensin-converting enzyme in the aorta, heart and kidney in rats, which resulted in higher NO production.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In line with this finding, Erbas et al (2007) reported that L-carnitine increased NO through reducing the activity of arginase and elevating that of NO synthase. Another study reported by Sharifi et al (2009) indicated that L-carnitine reduced the activity of angiotensin-converting enzyme in the aorta, heart and kidney in rats, which resulted in higher NO production.…”
Section: Discussionsupporting
confidence: 67%
“…Besides, L-carnitine participates in scavenging reactive oxygen species (Liu et al, 2004) and immunomodulation (Buyse et al, 2007). Erbas et al (2007) indicated that L-carnitine could increase plasma nitric oxide (NO) in human subjects. Nitric oxide is a potent vasodilator that opposes the onset of PHS in broiler chickens subjected to hypoxia (Khajali and Wideman, 2010).…”
mentioning
confidence: 99%
“…L-carnitine enhances myocardial function by improving fatty acid transport into the mitochondria (Ueland et al, 2012). Recently, Erbas et al (2007) indicated that L-carnitine could increase plasma nitric oxide (NO) in human subjects. Nitric oxide is a potent vasodilator that opposes the onset of PHS in broiler chickens (Khajali and Wideman, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, at physiological pH, the Vmax of each of the NOS enzymes was less than 1000-times that of arginase (21); therefore, it was concluded that both NOS and arginase could use arginine (22). Previously, we also showed that there was a negative relation between arginase enzyme activities and NO levels in breast cancer (15). Nitric oxide is a pervasive molecule that employs many biological outcomes (5).…”
Section: Serum Tissuementioning
confidence: 99%
“…Breast cancer tissue arginase activity was measured spectrophotometrically according to the tiosemicarbazide diacetylmonoxime urea (TDMU) method (15).…”
Section: Determination Of Argininase Enzyme Activity In Serummentioning
confidence: 99%